The Strategy of Rural Tourism Development Based on Green Economy Concept (A Study on Gubugklakah Village in Malang, East Java – Indonesia) - Havidz Ageng Prakoso (Jurnal Partisipatoris, 2022)
The purpose of the study was to examine how Gubugklakah Village becomes an International tourism object based on Green Economy concept. This study applied a qualitative design. The data from this study were analyzed comprehensively and descriptively. The results of the study showed that Gubugklakah Village has successfully performed Green Economy concept as a tourism object due to its consistency in providing an eco-friendly environment, natural resource, and human resource..